Class Shift of Proverbs in English Indonesian Translation on The Novel Entitled â€œThe Black Cat and Other Storiesâ€ Written by Edgar Allan Poe - Rubeka Ulfani; Bertaria Sohnata Hutauruk (TLEMC (Teaching and Learning English in Multicultural Contexts), 2022)
Proverbs are unique metaphoric expressions, and the translator should be familiar with their meanings in both the source language (SL) and the target language (TL), keeping in mind both of their similarities and distinctions. The research aims to find out the class shift and it is affected to the translation result on novel â€œThe Black Cat and Other Storiesâ€ by Edgar Allan Poe. This study focused on finding out types of class shift proverbs. This qualitative research method uses Catfordâ€™s theory about shift. The instrument of collecting data used by the researchers was documentation. The source of data were from the novel entitled â€œThe Black Cat and Other Storiesâ€ by Edgar Allan Poe and translated by Noura. This research resulted seven types of class shift on novel, namely (1) adjective shift into verb (15%), (2) Noun shift into adjective (15%), (3) adjective shift into noun (25%), (4) adjective shift into adverb (10%), (5) noun shift into verb (10%), (6) adverb shift into verb (10%), (7) verb shift into noun (15%). Therefore, the most dominant type of English class shift proverbs found in this novel is adjective shift into noun (25%).Â Keywords : Translation shift, Proverbs, Change of Meaning